COLLECTION AND CLASSIFICATION OF MARINE LITTER: OPPORTUNITY FOR ENVIRONMENTAL TRAINING OF UNIVERSITY STUDENTS - Carrazana García, Daymí Isabel; Fernández Blanco, Roberto; Martín Hernández, Alejandro (Centro Azúcar Journal, 2025)
Introduction: The collection and classification of marine litter can contribute from a citizen science perspective to the environmental training of students. Objective: To encourage active participation and skills among university students to address environmental problems related to unsustainable consumption habits and poor waste management through citizen science. Materials and Methods: The intervention took place in a natural coastal environment. A closed questionnaire was used to characterize the knowledge and attitude of young people about the environment and their knowledge about marine litter. A training workshop was held focusing on the content referred to and to guide the work of collecting and classifying marine litter on a beach according to material, possible original function and colour of the pieces. Results and Discussion: Although the theoretical knowledge of the topics covered is acceptably good, the workshop delved deeper into the subject and prepared the students for the task. This, together with a positive attitude and desire to learn, allowed two collections of marine litter on a beach and its classification. Plastic pieces associated with the food industry predominate, particularly flasks and lids. The most abundant colours are white, blue and black. Some have specimens of molluscs and cirripedians attached. Conclusions: The intervention contributed to the environmental education of students, fostered the development of research skills and reported data for researchers and managers who address the management of waste of anthropogenic origin.